AKTIVITAS PUBLIC RELATIONS DALAM MEMBINA HUBUNGAN BAIK Di APARTEMEN (Studi Deskriptif Kegiatan Di Apartemen Sunter Parkview) - Melati Banu; Galuh Sukmaranti (Oratio Directa (Prodi Ilmu Komunikasi), 2023)
Abstraction Not only in organizations or companies, the presence of public relations or public relations has a very large role in creating harmonization. Including harmonization in society and residents of an apartment or residence. For research techniques using a qualitative approach, namely data that is not measurable on a numerical scale. The data produced by the research are more concerned with the interpretation of the data found in the field. Theory of Excellence in Public Relations and the theory of participation become the analytical knife. Public relations and community relations are the main words in a social interaction. Keywords: Public relations, occupants, excellence in public relations